Regulation of thrombin activity by ligand-induced topological alteration in a thrombin-binding aptamer - Sasaki, Shogo; Ma, Yue; Hirokawa, Takatsugu; Ikebukuro, Kazunori; Tera, Masayuki; Nagasawa, Kazuo (Chemical communications (Cambridge, England), 2023)
Thrombin-binding aptamer (TBA), which forms a G-quadruplex (G4) structure with anti-parallel topology, interacts with thrombin to inhibit its enzymatic activity. Here we show that the G4-topology-altering ligand L2H2-2M2EA- 6LCO ( 6LCO ) changes the anti-parallel topology of TBA G4 to the parallel topology, thereby abrogating the thrombin-inhibitory activity of TBA. This finding suggests that G4 ligands that alter topology may be promising drug candidates for diseases involving G4-binding proteins. The function of the thrombin-binding aptamer was regulated by the G-quadruplex topology-altering ligand of L2H2-2M2EA- 6LCO , thereby controlling thrombin activity.